MODERN APPROACHES TO TEACHING FOREIGN LANGUAGES IN NON-LINGUISTIC HIGHER EDUCATION INSTITUTIONS: COMMUNICATIVE AND COMPETENCE-BASED ASPECTS - Abdullaeva, Roza Abdullaevna; Jumaniyazova, Nargiza Azatovna (SCIENCE and SOCIETY, 2026)
The article examines effective approaches to teaching foreign languages to students of non-linguistic faculties in higher education. It highlights the importance of communicative and competence-based methods in professionally oriented and time-limited instructional contexts.